Feminist Care Ethics Confronts Mainstream Philosophy - Hamington, Maurice; FitzGerald, Maggie (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue of Philosophies is devoted to dialogue between feminist care ethics and mainstream philosophical figures and concepts. As care ethics has evolved from its origins in the 1980s, it is clear that it does not always fit neatly within traditional philosophical categories. Yet, the philosophical implications of the ethics of care are robust and extend beyond ethics as such, with care theorists positing ontological, epistemological, and political significance to its approach. Despite these implications, and the growing acceptance of care ethics in a variety of academic literatures, it remains a somewhat marginalized philosophical framework. The original contributions to this volume juxtapose care theory with established philosophers and philosophical thought. The goal is to catalyze further intellectual interest and attention in how care enriches philosophy across a variety of subjects. In attending to both the intersections and interstices between care ethics and established philosophical theories and approaches, the contributions in this Special Issue provide a unique intellectual space for dialogue between significant philosophical figures and care ethics, with the aim of enriching both philosophical traditions. Accordingly, this Special Issue will appeal to scholars and practitioners from mainstream philosophy traditions, as well as those engaged with feminist philosophy, care theory, and the ethics of care.